(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare cross-training for the research sample in the transition period. And identify the impact of cross-training in some physical abilities of handball players. The researcher used the experimental method and the method of experimental and control equal groups. Thus، the sample was chosen in a deliberate way for the players of Al-Karkh Youth Club with ages (15-17) years and the number of (22) players. The researcher used cross-training during the transition period and the duration of the syllabus was 6 weeks. (12) training units two days per week and the training time was 90 minutes. The most important conclusions of the researcher is that the transition period if it has a positive rest period better than the negative rest and emerged through the results of the control and experimental groups. The most important recommendations are the need to invest the transitional period of training without resorting to the rest of the negative in order to maintain the level of players. Trainers must plan for the transition period with positive exercises that include recreational activities aimed at maintaining the level of physical players